1987
DOI: 10.1139/v87-025
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of geminal diazides: a novel route to 1,3,4-oxadiazoles

Abstract: The geminal diazides ethyl α,α-diazidoacetoacetate and α,α-diazidobenzoylacetate were prepared from the corresponding dibromo precursors by nucleophilic azide displacement. Thermolysis of the diazido compounds led to the formation of 2,5-disubstituted 1,3,4-oxadiazoles in high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 4 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…According to the authors, either the nitrene route with acyl migration in the intermediate 269 or an attack of the electron-rich nitrogen N-1 of the azide group on the carbonyl carbon giving zwitterion 270 may be considered in the formation of azidoazomethine 271 (Scheme 61). 109 The first photolysis of a-azido ketones was reported in 1964 by Edwards and Purushothaman. 75 The product of the irradiation of 2-azidocyclohexanone in hexane was assigned as 2-iminocyclohexanone on the basis of its IR characteristics, the easy polymerization of the obtained compound prevented the detailed structure elucidation.…”
Section: Thermolysis and Photolysis Of A-azido Ketonesmentioning
confidence: 99%
“…According to the authors, either the nitrene route with acyl migration in the intermediate 269 or an attack of the electron-rich nitrogen N-1 of the azide group on the carbonyl carbon giving zwitterion 270 may be considered in the formation of azidoazomethine 271 (Scheme 61). 109 The first photolysis of a-azido ketones was reported in 1964 by Edwards and Purushothaman. 75 The product of the irradiation of 2-azidocyclohexanone in hexane was assigned as 2-iminocyclohexanone on the basis of its IR characteristics, the easy polymerization of the obtained compound prevented the detailed structure elucidation.…”
Section: Thermolysis and Photolysis Of A-azido Ketonesmentioning
confidence: 99%
“…In the context of our ongoing research efforts, which concern the synthesis and reactivity of geminal di‐ and triazides, we realized that, in addition to the photochemical behavior of geminal diazides, a surprisingly small number of studies on the thermal decomposition of geminal diazides were reported . As we revised several of the early works on the thermolysis of geminal diazides, the study by Ogilvie and Rank reported in 1987 became the focus of our attention: A high‐yielding conversion of 2,2‐diazido acyl acetates 1 into 1,3,4‐oxadiazole‐2‐carboxylates 2 was described through simple heating of diazido starting compounds in xylene (Figure ) . The method does not require additional reagents and thus differs significantly from the alternative and more wide‐spread approaches toward this heterocyclic core, most of which are based on the chemistry of highly toxic hydrazides (Figure ) .…”
Section: Introductionmentioning
confidence: 98%
“…In 1987, Rank and co‐workers [ 43 ] reported the surprising formation of the 1,3,4‐oxadiazole core through diazide thermolysis. Although the reaction was only tested with two substrates, leading to 26a and 26b (Scheme 8A), we showed decades later that this reaction is of general appeal, allowing for the oxadiazole synthesis with a reasonably broad scope (Scheme 8B).…”
Section: Reactivities Of Geminal Diazidesmentioning
confidence: 99%